1991
DOI: 10.1002/ccd.1810230209
|View full text |Cite
|
Sign up to set email alerts
|

Accordion right coronary artery: An unusual complication of ptca guidewire entrapment

Abstract: The contour of the epicardial coronary vessels may change considerably during coronary angioplasty. We report the extreme and unique "accordion-like" wrinkling of the mid right coronary artery as a result of distal guidewire entrapment during coronary angioplasty. Recognition of this artifact and its treatment may prevent further complications of coronary angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…Others have reported decrease in flow through the affected vessel confirming that this phenomenon can be hemodynamically significant [2,5]. Therefore, the effects on flow patterns cannot be used to distinguish the etiology of the stenosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Others have reported decrease in flow through the affected vessel confirming that this phenomenon can be hemodynamically significant [2,5]. Therefore, the effects on flow patterns cannot be used to distinguish the etiology of the stenosis.…”
Section: Discussionmentioning
confidence: 90%
“…deformity consistent with invagination and the second resulted in a concentric defect, presumably from circumferential shortening and hence the ''accordion effect" as it was described. In an even more dramatic case, Deligonul et al [5] reported "the accordion effect" when a guidewire tip was incarcerated in a distal small branch of the right coronary artery. When the dilating catheter was withdrawn, traction on the guidewire resulted in severe vessel wall shortening and consequent "wrinkling" of the vessel and the angiographic appearance of a "corkscrew-like irregularity. "…”
Section: Discussionmentioning
confidence: 97%
“…Concertina in other words accordion effect is a pseudocomplication of PCI that mimics above cited real complications. The basic mechanism for the appearance of these pseudolesions is the straightening of a tortuous coronary artery along its luminal axis by relatively stiff intracoronary equipment, usually the guide wire, running down its length 2,[4][5][6] . Straightening the tortuous vessels with stiff guide wires makes it easy to pass the lesion with balloon and to dispose the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Concertina or accordion effect is an appearance of artifactual or pseudolesions during the course of PCI in tortuous vessels 1,2,3 . The possible mechanism suggested for accordion effect is straightening and shortening of tortuous artery by the stiff wire ended with invagination which showed up as a ''stair step deformity'' with contrast dye.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the RCA Mechanical straightening of a tortuous vessel during percutaneous transluminal coronary angioplasty (PTCA) has been well described [1,2]. This straightening has been termed an "accordion effect."…”
Section: Introductionmentioning
confidence: 99%